2019
DOI: 10.1016/j.jcot.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

No increased risk of acute osteomyelitis associated with closed or open long bone shaft fracture

Abstract: Objectives: Osteomyelitis of the long bones can result from hematogenous spread, direct inoculation or from a contiguous focus of infection. The association of osteomyelitis after long bone fractures has widely been believed to be true by practicing surgeons since the 1950s, even though the evidence has been poor. We hypothesized that long bone shaft fracture and major bone surgery are independent risk factors for osteomyelitis in adult trauma patients. Methods: The National Trauma Data Bank (NTDB) was queried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
1
2
1
2
Order By: Relevance
“…We also found that type of the fracture (open or close) is an independent risk factor for osteomyelitis (OR 6.25 CI 1.64–23.79). This contradicts the results of the study by Grigorian et al [ 22 ]. However, earlier studies showed results similar to ours [ 23 , 24 ].…”
Section: Discussioncontrasting
confidence: 94%
“…We also found that type of the fracture (open or close) is an independent risk factor for osteomyelitis (OR 6.25 CI 1.64–23.79). This contradicts the results of the study by Grigorian et al [ 22 ]. However, earlier studies showed results similar to ours [ 23 , 24 ].…”
Section: Discussioncontrasting
confidence: 94%
“…6 S. aureus is the most common cause of osteomyelitis in adults. 1,2,24,25 In our case and in some of these prior cases, it is possible that the osteomyelitis was subacute or chronic, resulting in weakening of the bone. In this theoretical context, these fractures would be considered pathological.…”
Section: Discussionmentioning
confidence: 62%
“…(Case 5 from 7 ), and Escherichia coli 6 . S. aureus is the most common cause of osteomyelitis in adults 1,2,24,25 …”
Section: Discussionmentioning
confidence: 99%
“…En los adultos es una patología menos frecuente y se encuentra mayormente asociada a factores de riesgo como traumatismos con alta probabilidad de infección (1). En casos traumáticos, se ha informado que la osteomielitis aguda ocurre con mayor frecuencia después de fracturas abiertas de huesos largos con incidencia de 4-63% (11). Por otro lado, las infecciones protésicas articulares representan una entidad relativamente nueva de osteomielitis, su incidencia oscila entre 1,5-2,5%, aunque se han reportado tasas de hasta 20% luego de la revisión quirúrgica (1).…”
Section: Epidemiologíaunclassified
“…Un estudio reciente realizado en España reveló que los niños con osteomielitis e554 fueron hospitalizados por un promedio de 13.5 días, que el 20% requirió cirugía y que el 2.3% desarrolló secuelas a largo plazo, como la discrepancia en la longitud de las piernas (12). Se ha descrito un aumento del número de casos de osteomielitis aguda de hasta 2,8 veces en los últimos 20 años lo que podría deberse a la mejora de las técnicas diagnósticas (11). La osteomielitis se considera una enfermedad con una alta tasa de secuelas, en especial en países de bajos recursos económicos, en los cuales los pacientes pueden llegar a desarrollar una enfermedad avanzada, crónica y asociada a complicaciones clínicas importantes y en algunos casos evolucionar hasta la muerte del paciente (1).…”
Section: Epidemiologíaunclassified